2018
DOI: 10.3389/fphys.2018.01178
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Mouse Genome Reveals Distinct Evolutionary and Functional Properties Among Circadian and Ultradian Genes

Abstract: In living organisms, biological clocks regulate 24 h (circadian) molecular, physiological, and behavioral rhythms to maintain homeostasis and synchrony with predictable environmental changes, in particular with those induced by Earth’s rotation on its axis. Harmonics of these circadian rhythms having periods of 8 and 12 h (ultradian) have been documented in several species. In mouse liver, harmonics of the 24-h period of gene transcription hallmarked genes oscillating with a frequency two or three times faster… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 62 publications
2
14
0
Order By: Relevance
“…Twelve-hour oscillation of Xbp1 in C. rota was previously reported [1]. These data combined with the recent independent report of an earlier evolutionary origin of genes cycling with a 12-h period [8] provide strong support for our hypothesis that the mammalian 12-h clock evolved from the circatidal clock.…”
Section: The 12-h Rhythms Of Gene Expression Are Evolutionarily Consesupporting
confidence: 84%
See 1 more Smart Citation
“…Twelve-hour oscillation of Xbp1 in C. rota was previously reported [1]. These data combined with the recent independent report of an earlier evolutionary origin of genes cycling with a 12-h period [8] provide strong support for our hypothesis that the mammalian 12-h clock evolved from the circatidal clock.…”
Section: The 12-h Rhythms Of Gene Expression Are Evolutionarily Consesupporting
confidence: 84%
“…The main line of evidences supporting the existence of a cell-autonomous mammalian 12-h clock include (1) the presence of intact hepatic 12-h rhythms of gene expression in circadianclock-deficient mice in vivo under free-running conditions [1,6]; (2) the detection of cell-autonomous 12-h rhythms of gene expression in mouse embryonic fibroblasts (MEFs) in a Bmal1-independent manner [1,6]; (3) that similar genes are regulated in a 12-h rhythmic manner in different organisms, indicating evolutionary conservation of these 12-h mechanisms [1]; and (4) that genes exhibiting 12-h rhythms arose much earlier during evolution than circadian genes [1,6,8]. It is hypothesized that circatidal clock mechanisms would have developed before the divergence of the major animal clades, existing in a common ancestor, occupying bodies of water in which tidal cycles would have been as ecologically important-if not more so-than the circadian cycle [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Castellana et al . observed that genes oscillating with a periodicity of about 12 hours are more likely to be evolutionary ancient and essential for cellular functions, suggesting that their short periodicity may reflect the periodicity of ancient clocks 49 . Short periodicities in the expression profile of several clock and clock-controlled genes in DD might suggest that not only the architecture but also the features of ancient endogenous clocks have been conserved in krill throughout speciation.…”
Section: Resultsmentioning
confidence: 99%
“…The different periodicity of gene expression impacts physiological outcomes [16] and may be related to transcriptional, translational and post-translational dynamics [17,18,19,20,21], as well as to phylogenetic and evolutionary components [22].…”
Section: Introductionmentioning
confidence: 99%